Endoscopic Transcanal Retrocochlear Approach to the Internal Auditory Canal with Cochlear Preservation: Pilot Cadaveric Study. (May 2016) - Kempfle, Judith; Kozin, Elliott D.; Remenschneider, Aaron K.; Eckhard, Andreas; Edge, Albert; Lee, Daniel J.
Contemporary operative approaches to the internal auditory canal (IAC) require the creation of large surgical portals for visualization with associated morbidity, including hearing loss, vestibular dysfunction, facial nerve injury, and skull base defects that increase the risk of cerebrospinal fluid leak. Transcanal approaches to the IAC have been possible only via a transcochlear technique. To preserve cochlear function, we describe a novel endoscopic transcanal infracochlear approach to the IAC in cadaveric temporal bones. Navigation fiducials were secured on fresh cadaveric heads, and real-time computed tomography imaging was used for surgical guidance. With a combination of curved instruments and rigid angled endoscopy, a transcanal hypotympanotomy and subcochlear tunnel were created with superior extension to access the IAC. Postprocedure imaging and temporal bone dissection confirmed access to the IAC without injury to the cochlea or neighboring neurovascular structures.